How Pesticides May Affect the Environment - Hurner, Laurie Ann (EDIS, 2017)
This article written for Citrus Industry Magazine, summarizes Chapter V, "Pesticides and the Environment" in book "Applying Pesticides Correclty" by Frederick Fishel. This article is an avenue for readers to take a quiz at the end of the article and submit it for one CORE CEU for their Flroida Restricted Use Pesticide License. Through this article readers should learn: the meaning of the word "environment", explain the difference between point-source and non-point source pollution, the routes by which pesticides can move offsite into the environment, how to prevent pesticide runoff, drift and movement as well as factors that affect as how to prevent: surface and groundwater contamination from pesticides and the effect of pesticides on non-target organisms including endandgered species.